Research on the Durability of Adhesive Composites - ROŚKOWICZ, Marek; SMAL, Tomasz (Engineering Transactions, 2014)
The paper presents research on the durability of adhesive composites, which may be used for the repair of technical objects. Durability of adhesive composites is understood in this paper as a material ability to transfer long lasting loads. Since that kind of information is not provided by manufacturers, the long-term strength and fatigue-life of selected adhesive composites are determined; especially with regard to their use in expedient (temporary) repairs of weapon systems. The results obtained show that safe values of the maximum long-term and fatigue loads of the adhesive composites investigated should be a half of the short-term strength obtained in a static tests.